2021
DOI: 10.1108/ebr-02-2021-0041
|View full text |Cite
|
Sign up to set email alerts
|

Radical innovation, incremental innovation, and competitive advantage, the moderating role of technological intensity: evidence from the manufacturing sector in Jordan

Abstract: Purpose The purpose of this paper is to identify the effect of radical innovation and incremental innovation on the competitive advantage of Jordanian industrial companies and identify the moderating role of technological intensity. Design/methodology/approach For this study’s purposes, 303 questionnaires from employees of 30 manufacturing firms were analysed. Convergent validity and discriminant validity tests were performed through structural equation modelling in the Smart-PLS programme. Data reliability … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
39
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 175 publications
(245 reference statements)
0
39
0
Order By: Relevance
“…Several studies in the literature, such as the studies of Anderson et al. (2014), Al-Khatib and Al-ghanem (2022) and Lin et al. (2013), confirmed that innovation is one of the main resources and determinants in creating CA.…”
Section: Introductionmentioning
confidence: 94%
See 3 more Smart Citations
“…Several studies in the literature, such as the studies of Anderson et al. (2014), Al-Khatib and Al-ghanem (2022) and Lin et al. (2013), confirmed that innovation is one of the main resources and determinants in creating CA.…”
Section: Introductionmentioning
confidence: 94%
“…A firm's ability to exploit resources and provide new products and services helps them establish innovation as a mainstay in their organizational and production activities (Lennerts et al, 2020). Several studies in the literature, such as the studies of Anderson et al (2014), Al-Khatib and Al-ghanem (2022) and Lin et al (2013), confirmed that innovation is one of the main resources and determinants in creating CA.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Mikalef et al (2020) emphasised that big data analytics can improve the radical and incremental innovation capabilities within companies. For instance, big data analytics can be used to assess new consumer patterns and latent preferences in customers, which can create innovative opportunities and new markets and may lead to competitive advantages (Al-Khatib and Al-ghanem, 2021).…”
Section: Intellectual Capital and Competitive Advantagementioning
confidence: 99%